Turbo bund former: Direct bund forming technology under straw mulch - Sood, Ashish; Dixit, Anoop; Modi, Rajesh U (Indian Farming, 2022)
Bund is the structure made by piling the soil mass employed to demarcate the field and apply irrigation effectively. Mostly, bunds are trapezoidal or triangular in shape and after water application through continuous use, they become semicircular. Moreover, flood irrigation is the most commonly used method to apply water to wheat sown fields that induce land and water degradation problems due to soil movement and water contamination. Bunds prevent degradation by arresting surface runoff and high erosive velocity of water during flood irrigation. It sensibly conserves water by solving water logging problems, especially in flood irrigated agricultural fields that further helps in stabilization of existing sub-soils. Bund divides the field into several compartments for equal distribution of water and restricts water loss. Thus, a turbo bund former is a machine that makes bunds in mulched fields for conserving soil with saving labour to the tune of 78% over the conventional bund forming method.